A strategy for evaluating the impact of processing of Chinese meteria medica on meridian tropism: the influence of salt-water processing of phellodendri chinensis cortex on renal transport proteins - Yang Chen; Fan Zhang; Wenjing Ren; Yue Zhou; Shiru Jiang; Shuo Zhang; Gui Xu; Xiutong Ge; Hui Gao (Frontiers in Pharmacology)
IntroductionThis study elucidated the potential mechanisms by which Phellodendri Chinensis Cortex with salt-water processing (SPC) enhances renal targeting efficacy, through investigating the effects of Phellodendri Chinensis Cortex (PC) on renal uptake and efflux transport capabilities before and after salt-water processing.MethodsThis study employed molecular docking, UPLC-TDQ-MS/MS, BCA, Western Blotting, and RT-PCR to assess the effects of raw Phellodendri Chinensis Cortex (RPC), SPC, berberine (BBR), and berberrubine (BBRR) on the transport capacity and expression of renal transport proteins OAT1, OAT3, OCT2, MATE1, MATE2K, P-gp, and MRP2 in HEK-293 cells.ResultsAnalyses demonstrated that BBR and BBRR exhibited a strong affinity for OCT2, P-gp, MRP2. Compared to RPC, SPC can increase the uptake capacity and expression of OCT2, while it can decrease efflux capacity and expression of P-gp and MRP2. Simultaneously, BBRR showed similar effects on OCT2, P-gp, and MRP2, compared to BBR. Therefore, the enhanced renal targeting effect of SPC can be attributed to the differential impact of the partial conversion of BBR to BBRR on the transport capacity of the renal transporters OCT2, P-gp, and MRP2.ConclusionThis study investigated the interactions between renal transporter proteins and drugs, with the objective of elucidating the mechanism by which SPC enhances renal targeting efficacy. The findings of this study offer new insights and methodologies for exploring the effects of Processing of Chinese Materia Medica (PCMM) on the meridian tropism of other traditional Chinese medicines (TCMs).